Associations between depressive symptoms, socio-economic factors, traumatic exposure and recent intimate partner violence experiences among women in Zimbabwe: a cross-sectional study - Mercilene Machisa; Simukai Shamu (BMC, 2022)
Abstract Background Population-based research on the cumulative effects of socio-economic conditions and trauma exposures, particularly women's experiences of intimate partner violence (IPV) on their mental health in Zimbabwe, has been limited. Aim Our study aimed to determine the associations between depressive symptoms and socio-economic factors, IPV, and traumatic exposures among a nationally representative sample of women from Zimbabwe. Methods Data was collected from 2905 women who volunteered to participate in a survey that had a multi-stage random sampling design. Depression was measured using the Centre for Epidemiologic Studies Depression Scale (CESD). Traumatic exposures included childhood trauma, life events, and experiences of IPV in the past year. We compared mean depression scores for different categories of variables, conducted linear regression modelling to investigate the bivariate and multivariate associations between variables and depressive symptoms' outcomes, and applied Structural Equation Modelling (SEM) to investigate the inter-relationships between variables and depressive symptoms' outcomes. Results Fifteen percent of women self-reported depressive symptoms (CESD score ≥ 21). Higher depressive symptomatology was associated with lower socio-economic status, experiencing IPV, history of childhood and other traumatic events, experiencing non-partner rape, and HIV positive status. Women who could find money in an emergency and sought informal or professional emotional support were less at risk of severe depressive symptoms. Conversely, seeking informal and formal social support was positively associated with more severe depressive symptoms. Conclusion This study contributes evidence showing that economic hardship, exposure to traumas including IPV, living with HIV, and low social support have a cumulative negative toll on mental health among Zimbabwean women from the general population. Programmes and services that respond to the mental ill-health effects reported by Zimbabwean women and prevention interventions that tackle the multiple risk factors for depression that we have identified must be prioritised.